IMPLEMENTASI SISTEM INFORMASI MAHASISWA PADA UNIVERSITAS BANI SALEH - Kresno Murti Prabowo; Yudiansyah Fauzi; Rifky Aditia Hamdan (Journal of Innovation And Future Technology, 2025)
In the digital era, efficient management of academic data has become a primary need for higher education institutions. Bani Saleh University faces challenges in managing student information which is still manual and less integrated, thus affecting the effectiveness of academic services. This research aims to develop and implement a Student Information System to increase the efficiency of academic administration, data accessibility, and speed in the service process.The methods used in this research include needs analysis, system design, development and testing of web-based systems. The system implemented includes main features such as student registration, academic data management, lecture schedules, and grade reporting. The research results show that the implementation of this information system can increase efficiency in data management, minimize errors in recording student information, and speed up the academic administration process.With this information system, Bani Saleh University can provide more optimal academic services for students and education staff. It is hoped that the implementation of this system can be a sustainable solution in supporting digital transformation in the higher education environment..